UPAYA PENINGKATAN PEMBERDAYAAN KADER DALAM PEMBERIAN PENDIDIKAN KESEHATAN DENGAN MENGGUNAKAN MEDIA LEMBAR BALIK IBU HAMIL DALAM DETEKSI DINI PENCEGAHAN ANEMIA DI WILAYAH PUSKESMAS ALALAK TENGAH KOTA BANJARMASIN - Isnaniah Isnaniah; Rubiati Hipni; Noorhayati Noorhayati; Mega Wasilah; Eryna Rezki Adella; Norhayati Norhayati (Jurnal Bakti untuk Negeri, 2021)
Anemia occurs by various factors, one of which is the problem of PKM partners. The problem with PKM partners is that the management of the posyandu in the Alalak Tengah Health Center area of ??Banjarmasin City is due to the limitations and lack of knowledge of cadres. Most of the Posyandu Cadre PKM partners have not implemented a good and correct Posyandu implementation flow, especially table 4 services, namely individual counseling, MCH counseling. Especially in early detection and prevention of anemia in pregnant women. The PKM implementation method consists of 3 main activities, namely: 1) Posyandu Cadre Training on early detection and prevention of anemia in pregnant women, 2) Assisting cadres in Posyandu to conduct MCH counseling, especially for pregnant women with anemia, one of early detection and prevention. anemia in pregnant women. 3) Evaluation of activities. The target of this activity is posyandu cadres in the work area of ??the Central Alalak Health Center using lecture, discussion, simulation and demonstration methods using flipcharts, then continued with mentoring and the formation of caring cadres from each posyandu representative. Then evaluation and monitoring of cadres concerned about early detection and prevention of anemia was carried out.